High-strength anti-aging PVC (polyvinyl chloride) lamplight film and preparation method thereof
By adding additives such as flame retardants and ultraviolet absorbers to the PVC lighting film, the problems of PVC lighting film being susceptible to heat aging and reduced light transmittance are solved, and high-intensity, aging resistance and flame retardant properties are achieved, extending service life and improving economic value.
Patent Information
- Application Number
- CN202510069245.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
The existing PVC lighting films are prone to heat aging during use, reduce light transmission, and have poor durability and decorative effects.
By adding mixed fillers such as flame retardants, ultraviolet absorbers, liquid flame retardants and powder flame retardants, the mechanical properties, flame retardants and aging resistance of PVC lighting films are improved, and the flexibility, hardness and decorative effect of the film are enhanced by adjusting the formula and adding different additives.
It realizes the high-intensity, aging resistance, flame retardant and ultraviolet resistance of PVC lighting film, extends the service life, expands the scope of application, and improves economic value.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lighting films, and in particular to a high-strength, ageing-resistant PVC lighting film and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a polymer formed by the polymerization of vinyl chloride monomers in the presence of initiators such as peroxides and azo compounds or under the action of light or heat according to the free radical polymerization mechanism. At present, PVC materials are widely used in building materials, industrial products, daily necessities, floor leather, floor tiles, artificial leather, pipes, wires and cables, packaging films, bottles, foaming materials, sealing materials, fibers, etc.
[0003] As an auxiliary item for every lamp, the lampshade not only plays the role of gathering illumination, concentrating light, and protecting eyes, but also has a strong decorative effect. Different lampshade materials have their own advantages and disadvantages. Only by choosing the most suitable one can the best effect be achieved. When people decorate the outdoors, they mostly stick PVC light film to the outdoor lighting system (such as neon lights and fluorescent lights) to make the outdoor lighting effect meet people's needs. Moreover, the common lampshade materials on the market are mainly glass and acrylic. Glass is brittle and prone to nicks or breakage during transportation, installation or use. Acrylic lampshades are also not scratch-resistant. The process of making acrylic lampshades is relatively complicated and the cost is also high. Moreover, during the use of PVC light film, the heat emitted by the lighting system during operation will cause the PVC light film to age due to heat, which will lead to a decrease in the light transmittance of the PVC light film. For this reason, the development of a PVC light film with good flexibility, uniform light transmittance, high strength, flame retardancy, and aging resistance has become a problem that needs to be solved in this field.
[0004] In view of this, we disclose a high-strength aging-resistant PVC lighting film and a preparation method thereof. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention aims to provide a high-strength, aging-resistant PVC lighting film and a preparation method thereof. The added mixed filler improves the mechanical properties and flame retardancy of the lighting film. By adding flame retardants, the PVC lighting film produced by the present application can obtain a better flame retardant grade and can withstand a higher thermal deformation temperature. By adding a compound of ultraviolet absorbers, liquid flame retardants, and powder flame retardants, the film will not deform even when exposed to ultraviolet rays for a long time, thereby expanding the scope of use of the product, extending the service life of the product, and improving the economic value of the product. By adding cold-resistant agents, toughening agents, etc., the multifunctional effect of the product can be further increased, so that the product has a wider range of applications.
[0006] To achieve the above object, the present invention proposes the following technical solutions:
[0007] A high-strength aging-resistant PVC lighting film, the PVC lighting film is prepared from the following raw materials in parts by weight:
[0008] 80~120 parts of PVC resin powder, 20~40 parts of plasticizer, 8~15 parts of cold-resistant agent, 0.2~0.5 parts of ultraviolet absorber, 0.2~0.6 parts of antioxidant, 2~5 parts of stabilizer, 0.2~0.6 parts of mildew and antibacterial agent, 5~15 parts of heavy calcium carbonate, 1~3 parts of titanium dioxide, 8~15 parts of liquid flame retardant, 2~4 parts of powder flame retardant, 0.005~0.015 parts of pigment and 0.02~0.06 parts of whitening agent.
[0009] The mildew and antibacterial agent is nitrogen-containing nano zinc oxide;
[0010] The powder flame retardant is aminated MXenen;
[0011] The liquid flame retardant is a phosphorus-based environmentally friendly liquid flame retardant.
[0012] On the basis of the above scheme and as a preferred scheme of the above scheme, the aminated MXenen is obtained by etching MXenen with ZnCl2 and then aminating it with ethylenediamine; the phosphorus-based environmentally friendly liquid flame retardant is modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0013] On the basis of the above scheme and as a preferred scheme of the above scheme, the cold-resistant agent is di(2-ethylhexyl) adipate, and the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0014] On the basis of the above scheme and as a preferred scheme of the above scheme, the ultraviolet absorber is ultraviolet absorber UV-531.
[0015] On the basis of the above scheme and as a preferred scheme of the above scheme, the stabilizer is a barium zinc stabilizer.
[0016] On the basis of the above scheme and as a preferred scheme of the above scheme, the whitening agent is 2.5-bis(5-tert-butyl-2-benzoxazolyl)thiophene.
[0017] On the basis of the above scheme and as a preferred scheme of the above scheme, the plasticizer is one of di(2-ethylhexyl) adipate, pentaerythritol tetrapentanoate, phosphorus-based flame retardant, tri(1-chloro-2-propyl) phosphate, tetrabromophthalic anhydride, triester phosphate and diester phosphate.
[0018] On the basis of the above scheme and as a preferred scheme of the above scheme, the method for preparing the high-strength aging-resistant PVC lighting film comprises the following steps:
[0019] S1. Pre-mix the liquid flame retardant and the powder flame retardant according to the mass fraction to obtain a mixed intermediate, and then add the mildew and antibacterial agent at the same stirring speed and stir for 0.2-0.5h; then increase the stirring speed to the second-order stirring speed, add a cold-resistant agent, an ultraviolet absorber, an antioxidant, a stabilizer, a mildew and antibacterial agent, titanium dioxide, a pigment, a whitening agent, a plasticizer and heavy calcium carbonate to obtain a premixed material powder, and then put the premixed material and the PVC resin powder into a high-speed mixer, and mix them evenly in the high-speed mixer to obtain a mixed powder;
[0020] S2. The mixture is transferred to the planetary extruder for mixing, and after mixing evenly, it is extruded from the die head;
[0021] S3. After mixing and plasticizing, the mixture is transported to a filter for filtration;
[0022] S4. The filtered mixture is transported to a rubber tape machine for roller calendering into a film;
[0023] S5. The calendered PVC film is cooled, trimmed and rolled;
[0024] S6. After the calendered film enters the printing press, the ink is printed on the PVC film through the printing cylinder of the printing press;
[0025] S7. After printing is completed, the PVC film is placed in a dryer for drying to ensure that the printed pattern is firm and not easy to fall off;
[0026] S8. The dried PVC film is cut and rolled into a roll to obtain a finished product.
[0027] On the basis of the above scheme and as a preferred scheme of the above scheme, the mixing stirring speed of the liquid flame retardant and the powder flame retardant is 150rpm-250rpm, the second-stage stirring speed is 450rpm-850rpm, and the stirring speed of the high-speed mixer is 950rpm-1050rpm.
[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0029] The present invention discloses a high-strength, anti-aging PVC lighting film and a preparation method thereof. The multifunctionality of the PVC film is enhanced by adding different additives: the added two-dimensional material is the main powder flame retardant, the modified nano zinc oxide is used as an anti-mildew and antibacterial agent, and the modified DOPO is used as a liquid flame retardant. The powder flame retardant and the liquid flame retardant are compounded and used, and the large steric effect and molecular cross-linking structure in the liquid flame retardant are utilized. The molecules contain polar functional groups, which repel the polarity in the system, thereby reducing the possibility of raw material agglomeration. After the two are mixed, they are attached to the active sites of the modified two-dimensional material. On the basis of satisfying the uniform mixing of the added filler and the matrix and ensuring the mechanical properties, it has excellent flame retardant properties and anti-aging effects, and can prevent deformation even when exposed to ultraviolet rays for a long time. Moreover, the haze value and transparency of the PVC film of the present invention are used in combination with the standard, and its hardness value can also meet the requirements of film scratch resistance, thereby meeting more usage scenarios.
[0030] The PVC lighting film of the present invention has the following advantages:
[0031] 1. PVC resin is the main component, to which cold-resistant plasticizers, stabilizers, mildew inhibitors, antioxidants, and flame retardants are added, which can make the product have the properties of cold resistance, aging resistance, mildew resistance, antibacterial resistance, flame retardancy, and UV resistance, and has strong functionality.
[0032] 2. The flexibility, hardness, aging resistance, UV resistance and other properties of PVC light film can be changed by adjusting the formula; at the same time, different colorants can be added to the formula or the calendered film can be directly digitally printed to achieve a variety of decorative effects, providing more possibilities for the application design of PVC light film.
[0033] 3. PVC material is not only cheap, but also has a lower density, lighter weight, and is easier to install and transport than glass and acrylic materials. Therefore, PVC lighting film is more suitable for mass production and consumption.
[0034] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered part of the present subject matter disclosure to the extent such concepts are not mutually inconsistent.
[0035] The foregoing and other aspects, embodiments and features of the present invention will be more fully understood from the following description. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or will be learned from the practice of the specific embodiments according to the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0037] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. "Include" or "comprise" and other similar words mean that the elements or objects appearing before "include" or "comprise" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0038] In the present invention, the liquid flame retardant is a phosphorus-containing liquid flame retardant. 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, DOPO, is a novel flame retardant intermediate, which contains a PH bond in its structure and is highly active to olefins, epoxy bonds and carbonyl groups. Furthermore, the phosphorus-containing liquid flame retardant is a modified DOPO, which is specifically prepared by the Atherton-Todd reaction, using the PH bond in DOPO to react with the hydroxyl group in the alcohol compound under the action of carbon tetrachloride, and the specific reaction process is as follows:
[0039] Place half the volume of dichloromethane in a round-bottom flask, add DOPO and triethylamine into the round-bottom flask in sequence and stir with a magnetic force, wherein the molar ratio of DOPO to triethylamine is 10:11. After DOPO is completely dissolved, add an amount of N-[2,2-dimethyl-(4-hydroxy)]acrylamide equal to that of triethylamine into the mixture, stir with a magnetic force at the same stirring speed to obtain a uniform mixture.
[0040] The uniform mixture is placed in an ice water bath and cooled to 0°C, and then carbon tetrachloride with triethylamine and other substances is added dropwise to the uniform mixture. After the addition is completed, the reaction is carried out at room temperature for 12 hours. The product after the reaction is completed is diluted with two-thirds of the volume of dichloromethane in the container, and then extracted with deionized water and saturated brine. The organic layer is dried with MgSO4 and filtered. The solvent is removed by vacuum distillation to obtain a yellow liquid. The yield of modified DOPO produced by this method is about 89%. In order to improve the purity of modified DOPO, it is purified by dissolving in an organic solution and then distilling under reduced pressure. Ethyl acetate is used for dissolution, stirring evenly, and then vacuum distillation is carried out at 45°C until the solvent is completely evaporated to obtain a viscous liquid. The purified modified DOPO needs to be used within 60 hours to avoid material deterioration affecting the performance of the membrane.
[0041] In the modified DOPO, due to the presence of two benzene rings and tertiary carbon structures, a stable quasi-crosslinking structure is formed in space. Coupled with the steric hindrance effect, the rigidity is enhanced, and the mechanical strength of the film can be strengthened to a certain extent. When encountering an open flame or high light intensity, the phosphorus element in the modified DOPO will produce phosphorus-containing free radicals. The phosphorus-containing free radicals can capture highly active free radicals and react with them, thereby reducing the chance of combustion or reducing the damage of light intensity to the matrix, playing a role in quenching flames and resisting light aging. In the late stage of combustion or long-term accumulation of light energy, after a period of time, the modified DOPO will decompose to produce phosphoric acid compounds, which can promote the formation of a phosphorus-containing carbon layer in the PVC resin matrix, which can increase the residual carbon rate and the integrity of the carbon layer during the combustion process. The layer structure can also weaken the damage of light to the PVC matrix, and ultimately enhance the flame retardant and aging resistance of the film.
[0042] Furthermore, the mildew and antibacterial agent is nitrogen-containing nano zinc oxide, specifically, the nano zinc oxide particles are ultrasonically washed with an alcohol-water mixture, and then air-dried for standby use. At the same time, N-phenylmaleimide (N-PMI, >95.0%) is configured into a 10wt% acetone solution, and then the air-dried nano zinc oxide is immersed in the acetone solution of N-PMI, and stirred at 350rpm after immersion for 2h. After at least three "solution immersion-stirring", it is fished out and placed in a 60°C oven for drying for 2h to obtain nitrogen-containing nano zinc oxide. The N-PMI is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Nano zinc oxide has anti-ultraviolet and antibacterial effects, and N-phenylmaleimide has excellent properties such as high temperature resistance, moisture resistance, and aging resistance, so that the film added with nitrogen-containing nano zinc oxide has good light aging resistance. Moreover, when the light energy is strong and has a burning tendency, N-phenylmaleimide burns and heats to produce 2π+π ring cross-linking, which can improve the film's anti-dripping property.
[0043] Furthermore, the powder flame retardant is an aminated two-dimensional material, and the specific operation steps are:
[0044] MXene and ZnCl2 were fully mixed in a glove box at a molar ratio of 1:1.5, placed in an alumina crucible, and then heated at 550 °C for 5 h in a tube furnace under argon. ZnCl2 exists in a molten state at 550 °C and ionizes into Zn 2+ ions. Then, we obtain Zn with strong electron capacity. 2+ The Zn atoms can diffuse into the middle layer of MXene to produce a new MAX phase, thus completing the ZnCl2 etching of MXene. After etching, it can have a larger specific surface area, and ZnCl2 etching can effectively remove oxides and impurities on the surface of MXene, improve its catalytic performance, and thus improve the activity and stability of the catalyst. Then, ethylenediamine is prepared into a solution for amination to obtain aminated MXene.
[0045] The introduction of amino MXenen, on the basis of enhancing the mechanical properties of the film, the polar groups can utilize the attraction between the positive and negative dipoles of the molecules to form molecular aggregation between the surfaces of materials such as heavy calcium carbonate, strengthen the interfacial bonding force, and thus enhance the aging resistance of the film.
[0046] Moreover, when mixing the materials, the liquid flame retardant and the powder flame retardant are pre-stirred to obtain a mixed intermediate, so that a suspension mixed intermediate with low viscosity can be formed. There are polar functional groups between the liquid flame retardant and the powder flame retardant, and the polar repulsion between the molecules reduces the possibility of flame retardant agglomeration; further adding antifungal and antibacterial agents and increasing the stirring speed, using the voids in the etched MXene material to attach and fix on the active sites on the surface of the material, can reduce the possibility of material agglomeration, and as more additives are added, the intermolecular forces between the liquid flame retardant, the powder flame retardant, and the antifungal and antibacterial agent can be weakened without affecting the efficacy of the three. Under ideal conditions, the molecular particles of the liquid flame retardant and the antifungal and antibacterial agent should be spaced apart on the active sites of the powder flame retardant material.
[0047] Furthermore, the stabilizer is a barium zinc stabilizer. Liquid barium zinc composite stabilizer is generally a light yellow to yellow clear liquid, with a specific gravity of 0.95-1.02 at room temperature, a viscosity of less than 100 cP, and a freezing point of -15°C. The barium zinc stabilizer selected in the present invention has a specific gravity of 0.98 at room temperature, similar to liquid barium zinc. The barium zinc stabilizer has excellent heat and light stability, low initial colorability, good transparency and color stability. Their stabilizing effect is stronger than that of solid composite soaps, so the dosage can be reduced, generally 2-5 parts, dust poisoning will not occur, and it is completely dissolved in general plasticizers, has good dispersibility, and has a small tendency to precipitate.
[0048] In a further aspect, the plasticizer is one of di(2-ethylhexyl) adipate, pentaerythritol tetrapentanoate, phosphorus flame retardant, tri(1-chloro-2-propyl) phosphate, tetrabromophthalic anhydride, phosphate triester and phosphate diester. Phosphate plasticizers have good heat resistance and weather resistance, which helps to improve the service life of the film.
[0049] Example 1
[0050] A high-strength aging-resistant PVC lighting film, the PVC lighting film is prepared from the following raw materials in parts by weight:
[0051] 100 parts of PVC resin powder, 30 parts of plasticizer, 12 parts of cold-resistant agent, 0.3 parts of ultraviolet absorber, 0.4 parts of antioxidant, 3 parts of stabilizer, 0.4 parts of mildew and antibacterial agent, 12 parts of heavy calcium carbonate, 2 parts of titanium dioxide, 11 parts of liquid flame retardant, 3 parts of powder flame retardant, 0.010 parts of pigment and 0.04 parts of whitening agent.
[0052] Among them, the mildew and antibacterial agent is amino MXenen; the powder flame retardant is nitrogen-containing nano zinc oxide; and the liquid flame retardant is a phosphorus-based environmentally friendly liquid flame retardant.
[0053] Furthermore, the aminated MXenen is obtained by etching MXenen with ZnCl2 and then aminating it with ethylenediamine; and the phosphorus-based environmentally friendly liquid flame retardant is modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0054] In this embodiment, the cold-resistant agent is di(2-ethylhexyl) adipate, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; the ultraviolet absorber is ultraviolet absorber UV-531; the stabilizer is barium zinc stabilizer; the whitening agent is 2.5-bis(5-tert-butyl-2-benzoxazolyl)thiophene; and the plasticizer is triester phosphate.
[0055] Furthermore, the method for preparing the high-strength aging-resistant PVC lighting film comprises the following steps:
[0056] S1. Pre-mix the liquid flame retardant and the powder flame retardant according to the mass fraction to obtain a mixed intermediate, and then add the mildew and antibacterial agent at the same stirring speed and stir for 0.35h; then increase the stirring speed to the second-order stirring speed, add a cold-resistant agent, an ultraviolet absorber, an antioxidant, a stabilizer, a mildew and antibacterial agent, titanium dioxide, a pigment, a whitening agent, a plasticizer and heavy calcium carbonate to obtain a premixed material powder, and then put the premixed material and the PVC resin powder into a high-speed mixer, and mix them evenly in the high-speed mixer to obtain a mixed powder;
[0057] S2. The mixture is transferred to the planetary extruder for mixing, and after mixing evenly, it is extruded from the die head;
[0058] S3. After mixing and plasticizing, the mixture is transported to a filter for filtration;
[0059] S4. The filtered mixture is transported to a rubber tape machine for roller calendering into a film;
[0060] S5. The calendered PVC film is cooled, trimmed and rolled;
[0061] S6. After the calendered film enters the printing press, the ink is printed on the PVC film through the printing cylinder of the printing press;
[0062] S7. After printing is completed, the PVC film is placed in a dryer for drying to ensure that the printed pattern is firm and not easy to fall off;
[0063] S8. The dried PVC film is cut and rolled into a roll to obtain a finished product.
[0064] The mixing speed of the liquid flame retardant and the powder flame retardant is 200 rpm, the second-stage mixing speed is 650 rpm, and the mixing speed of the high-speed mixer is 1000 rpm.
[0065] Example 2
[0066] Different from the above-mentioned embodiment 1, a high-strength aging-resistant PVC lighting film is prepared from the following raw materials in parts by weight:
[0067] 80 parts of PVC resin powder, 20 parts of plasticizer, 8 parts of cold-resistant agent, 0.2 parts of ultraviolet absorber, 0.2 parts of antioxidant, 2 parts of stabilizer, 0.2 parts of mildew and antibacterial agent, 5 parts of heavy calcium carbonate, 1 part of titanium dioxide, 8 parts of liquid flame retardant, 2 parts of powder flame retardant, 0.005 parts of pigment and 0.02 parts of whitening agent.
[0068] In the raw material mixing process S1, the mixing stirring speed of the liquid flame retardant and the powder flame retardant is 150 rpm, the second-stage stirring speed is 450 rpm, and the stirring speed of the high-speed mixer is 950 rpm.
[0069] Example 3
[0070] Different from the above-mentioned embodiment 1, a high-strength aging-resistant PVC lighting film is prepared from the following raw materials in parts by weight:
[0071] 120 parts of PVC resin powder, 40 parts of plasticizer, 15 parts of cold-resistant agent, 0.5 parts of ultraviolet absorber, 0.6 parts of antioxidant, 5 parts of stabilizer, 0.6 parts of mildew and antibacterial agent, 15 parts of heavy calcium carbonate, 3 parts of titanium dioxide, 15 parts of liquid flame retardant, 4 parts of powder flame retardant, 0.015 parts of pigment and 0.06 parts of whitening agent.
[0072] In the raw material mixing process S1, the mixing stirring speed of the liquid flame retardant and the powder flame retardant is 250 rpm, the second-stage stirring speed is 850 rpm, and the stirring speed of the high-speed mixer is 1050 rpm.
[0073] Comparative Example 1
[0074] Different from Example 1, in step S1, PVC resin powder, plasticizer, cold-resistant agent, ultraviolet absorber, antioxidant, stabilizer, mildew and antibacterial agent, heavy calcium carbonate, titanium dioxide, liquid flame retardant, powder flame retardant, pigment and brightener are put into a high-speed mixer according to their mass fractions after being measured, and mixed evenly in the high-speed mixer to obtain a mixed powder.
[0075] For other steps and processes, refer to Example 1.
[0076] Comparative Examples 2-8
[0077] The difference from Example 1 is that the components shown in Table 1 are weighed by weight percentage: PVC resin powder, plasticizer, cold-resistant agent, ultraviolet absorber, antioxidant, stabilizer, mildew and antibacterial agent, heavy calcium carbonate, titanium dioxide, liquid flame retardant, powder flame retardant, pigment and brightener. The PVC light film is prepared according to the process of Example 1. Except for the different component contents, other steps and processes refer to Example 1. The component contents of Comparative Examples 2-8 are shown in Table 1:
[0078] Table 1 Material ratios for comparative examples 2-8
[0079] Performance Testing
[0080] Mechanical properties test
[0081] The mechanical properties test includes two aspects: tensile strength and elongation at break. The tensile strength and elongation at break are tested in accordance with GB / T 1040.2-2006. According to relevant test requirements and regulations, the sample size is uniformly controlled to 185mm×20mm×2mm; further, the test speed in the tensile strength test is 50 mm / min, and the test speed in the tensile elastic modulus test is 1 mm / min.
[0082] UV aging resistance test
[0083] According to the standard sample preparation for the mechanical properties test of light film, the film samples of the same size were placed in the ultraviolet irradiation box for 800 hours, and the changes in the film surface morphology were observed. The angle and distance of the sample from the ultraviolet light source were kept consistent.
[0084] Flame retardant properties
[0085] The flame retardant performance test of the sample of the present invention includes two aspects of comparative reference: oxygen index and flame retardant grade. The sample is prepared with reference to the standard GB / T 2406.2-2009 to test the oxygen index of the film; the flame retardant grade of the film is tested according to the UL-94 standard, the sample size is 125mm×12.7mm×3.2mm, and the test standard refers to ASTMD3801.
[0086] Light transmission performance
[0087] The light transmittance of the sample is also an important indicator. The light transmittance and haze of the material are tested in accordance with GB / T 2410-2008. The shear film specification is a 50mm*50mm square piece that can cover the entrance window of the integrating sphere. Three samples are sheared in each group, and the haze value, transparency, and yellowness value are tested using a haze meter, and the results are averaged.
[0088] Surface hardness performance test
[0089] The surface hardness test of the sample film was carried out with reference to GB / T6739-1996 "Pencil Determination of Coating Hardness". The films of Examples 1-3 and Comparative Examples 1-8 were spread on a 70mm*150mm*(0.45-0.8)mm thin steel test plate to ensure that the film could not be wrinkled during the pencil scratching process. According to the requirements of Method B (i.e., manual method), the prepared high-grade drawing pencils: 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B were used for scratch measurement, among which 3H was the hardest and 6B was the softest.
[0090] The PVC lighting films of the above-mentioned Examples 1-3 and Comparative Examples 1-8 were cut into standard samples, and performance tests and analyses were performed according to the standards. The results are shown in Table 2.
[0091] Table 2 Test results analysis table
[0092] From the analysis of the comparison results in Table 2 above, it can be seen that if the material mixing mode is directly adopted, the difference in tensile strength and the data deviation will be large, which is caused by the uneven dispersion of the materials in the matrix. In the influence of a single element on the mechanical properties of the film, the presence of two-dimensional materials in the powder flame retardant has a more obvious effect on the mechanical results, followed by the effect of the antifungal and antibacterial agent of nano zinc oxide. The simultaneous absence of two-dimensional materials and nanoparticles will cause a sharp decline in the mechanical properties of the film.
[0093] For flame retardant properties, it can also reflect certain light aging resistance and durability. When PVC light film is exposed to high-energy light, the existing lampshade light film has the problem of not being resistant to high-intensity light exposure. We directly use flame retardant properties as one of the means to evaluate light aging resistance. Among them, as a single element, liquid flame retardant has the greatest impact on the flame retardant properties of the film, followed by powder flame retardant, and finally the influence of mildew and antibacterial agent. For the lack of compound type, the compound use of powder flame retardant and liquid flame retardant, liquid flame retardant and mildew and antibacterial agent can effectively adhere to the active sites of powder flame retardant, and can form NP flame retardant system. The compound use of the three can achieve the effect of 1+1+1>3. The surface changes after 800 hours of ultraviolet irradiation also confirm this conclusion. When the mixing method of the present invention is not used, the reason for the microcracks on the surface after 800 hours of ultraviolet irradiation is that the uneven texture of the film causes the light-irradiated area to be too weak, resulting in microcracks.
[0094] Furthermore, the powder flame retardant and the liquid flame retardant are compounded and used, and the large steric effect and molecular cross-linked structure in the liquid flame retardant are utilized, and the molecules contain polar functional groups, which repel the polarity in the system, thereby reducing the possibility of raw material agglomeration. After the two are mixed, they are attached to the active sites of the modified two-dimensional material, and on the basis of satisfying the addition of fillers and the uniform mixing of the matrix and ensuring the mechanical properties, it has excellent flame retardant properties and aging resistance. Moreover, the haze value and transparency of the PVC film of the present invention are combined with the use standard, and its hardness value can also meet the requirements of film scratch resistance, thereby being able to meet more usage scenarios.
[0095] By adding flame retardants, the PVC lighting film of the present invention can achieve a better flame retardant grade and withstand a higher heat deformation temperature. By adding a combination of ultraviolet absorbers, liquid flame retardants and powder flame retardants, the film will not deform even when exposed to ultraviolet rays for a long time. The film is suitable for use as a lampshade in homes and public facilities, which expands the scope of use of the product, extends the service life of the product, and improves the economic value of the product. By adding cold-resistant agents, toughening agents, etc., the multifunctional effect of the product can be further increased, so that the product has a wider range of applications.
[0096] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A high-strength, aging-resistant PVC lighting film, characterized in that: The PVC lighting film is prepared from the following raw materials in parts by weight: 80~120 parts of PVC resin powder, 20~40 parts of plasticizer, 8~15 parts of cold-resistant agent, 0.2~0.5 parts of ultraviolet absorber, 0.2~0.6 parts of antioxidant, 2~5 parts of stabilizer, 0.2~0.6 parts of mildew and antibacterial agent, 5~15 parts of heavy calcium carbonate, 1~3 parts of titanium dioxide, 8~15 parts of liquid flame retardant, 2~4 parts of powder flame retardant, 0.005~0.015 parts of pigment and 0.02~0.06 parts of whitening agent.
2. The high-strength, anti-aging PVC lighting film according to claim 1, characterized in that: The mildew and antibacterial agent is nitrogen-containing nano zinc oxide; The powder flame retardant is aminated MXenen; The liquid flame retardant is a phosphorus-based environmentally friendly liquid flame retardant.
3. The high-strength, anti-aging PVC lighting film according to claim 1, characterized in that: The aminated MXenen is obtained by etching MXenen with ZnCl2 and then aminating it with ethylenediamine; the phosphorus-based environmentally friendly liquid flame retardant is modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
4. The high-strength aging-resistant PVC lighting film according to claim 1, characterized in that: The cold-resistant agent is di(2-ethylhexyl) adipate, and the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
5. The high-strength, anti-aging PVC lighting film according to claim 1, characterized in that: The ultraviolet absorber is ultraviolet absorber UV-531.
6. The high-strength anti-aging PVC lighting film according to claim 1, characterized in that: The stabilizer is a barium zinc stabilizer.
7. The high-strength, anti-aging PVC lighting film according to claim 1, characterized in that: The brightener is 2.5-bis(5-tert-butyl-2-benzoxazolyl)thiophene.
8. The high-strength, anti-aging PVC lighting film according to claim 1, characterized in that: The plasticizer is one of di(2-ethylhexyl) adipate, pentaerythritol tetrapentanoate, phosphorus-based flame retardant, tri(1-chloro-2-propyl) phosphate, tetrabromophthalic anhydride, triester phosphate and diester phosphate.
9. A method for preparing the high-strength aging-resistant PVC lighting film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Pre-mix the liquid flame retardant and the powder flame retardant according to the mass fraction to obtain a mixed intermediate, and then add the mildew and antibacterial agent at the same stirring speed and stir for 0.2-0.5h; then increase the stirring speed to the second-order stirring speed, add a cold-resistant agent, an ultraviolet absorber, an antioxidant, a stabilizer, a mildew and antibacterial agent, titanium dioxide, a pigment, a whitening agent, a plasticizer and heavy calcium carbonate to obtain a premixed material powder, and then put the premixed material and the PVC resin powder into a high-speed mixer, and mix them evenly in the high-speed mixer to obtain a mixed powder; S2. The mixture is transferred to the planetary extruder for mixing, and after mixing evenly, it is extruded from the die head; S3. After mixing and plasticizing, the mixture is transported to a filter for filtration; S4. The filtered mixture is transported to a rubber tape machine for roller calendering into a film; S5. The calendered PVC film is cooled, trimmed and rolled; S6. After the calendered film enters the printing press, the ink is printed on the PVC film through the printing cylinder of the printing press; S7. After printing is completed, the PVC film is placed in a dryer for drying to ensure that the printed pattern is firm and not easy to fall off; S8. The dried PVC film is cut and rolled into a roll to obtain a finished product.
10. The method for preparing a high-strength anti-aging PVC lighting film according to claim 8, characterized in that: The mixing speed of the liquid flame retardant and the powder flame retardant is 150 rpm-250 rpm, the second-stage stirring speed is 450 rpm-850 rpm, and the stirring speed of the high-speed mixer is 950 rpm-1050 rpm.
Citation Information
Patent Citations
PVC (Polyvinyl Chloride) modified material for sunlight fabric and preparation method thereof
CN106947187A
Preparation method of efficient phosphorus flame retardant
CN115232362A
Flame-retardant MXene / polymer composite aerogel and preparation method thereof
CN117720795A
Preparation method of anti-fouling anti-aging high-flame-retardant art wall cloth
CN119036876A